Persepsi Masyarakat Baduy terhadap Konflik: Pemeliharaan Budaya dan Penyelesaian Tradisional dalam Era Perubahan - Puryanto, Sidik; Sardjiyo (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
This research explores the Baduy community in Kanekes, a traditional Sundanese community in the Kendeng Mountains region of South Banten. The Baduy community possesses distinct cultures, traditions, and social systems from the majority in their vicinity, adhering to inherited rules and norms. The study aims to investigate the Baduy community's understanding of conflicts and how they resolve conflicts based on their customary rules. The research methodology employed is qualitative descriptive, collecting data through questionnaires and structured interviews from 10 respondents within the outer Baduy community. The results show that the Baduy community possesses a sound understanding of conflicts, views conflicts as part of life, and tends to resolve them peacefully based on cultural values and customary norms. The conflicts that arise encompass romantic conflicts, psychological conflicts, conflicts with modern culture, and conflicts related to natural resources. The effectiveness of traditional conflict resolution is evident in the Baduy community's ability to maintain peace, utilize customary values as guidelines, and leverage the crucial role of traditional leaders in mediating and resolving conflicts. The Baduy community remains steadfast in their adherence to customary values in facing challenges of social change and the environment to preserve their unique culture and traditions. In-depth understanding of conflicts and the resolution methods used by the Baduy community provides valuable insights to support cultural preservation and effective conflict resolution within this community.